GATI LAMBANGSIH LARAS SLENDRO PATHET MANYURA SEBAGAI KARYA INOVASI KARAWITAN GAYA YOGYAKARTA: KAJIAN MUSIKALITAS DAN KARAKTER GENDING - Anon Suneko; Trustho Trustho; Salsa Bila (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2021)
Gati Lambangsih laras slendro pathet manyura is one of the Yogyakarta musical styles which was created during the reign of Sri Sultan Hamengku Buwono X. This new creation in the ladrang format complements Beksan Bedaya's aesthetic Lambangsari, which was held at the Uyon-Uyon Hadiluhung event on December 28, 2020, at Kagungan Dalem Ward Srimanganti. Unlike other gending Gati, Gati This symbol is presented with a slendro-barreled gamelan in collaboration with brass section western wind music. Of course, the new taste of Gending Gati cannot be separated from the motivation and concept of its creation. However, musically, working and blending Gamelan and brass sections require carefulness in achieving harmony in the musical presentation.